Development of Student Worksheets (LKPD) based on the 5E Learning Cycle on the Material of Locomotor Systems in Grade XI of Senior High School - Nababan, Angelica; Martina Restuati (Bioilmi: Jurnal Pendidikan, 2025)
This study was conducted to address issues in schools, such as students' lack of understanding of the material, the use of conventional learning models, and limited use of learning media. The main goal of the research was to develop a valid, practical, and effective LKPD  based on the Learning Cycle 5E model for biology lessons, specifically on the topic of the Movement System for 11th grade students at Kartika I-2 High School in Medan. This research followed the 4D development model, with data collected through observations, interviews, tests, and questionnaires.The study used several data collection instruments: teacher interview sheets, material, learning, and media validation questionnaires, teacher and student response questionnaires, and pretest and posttest questions. The results showed that the validation by material experts resulted in an average percentage of 90.6%, classified as "very feasible." Validation by learning experts showed 84.6%, also categorized as "very feasible," while media expert validation resulted in 90%, considered very feasible.The practicality of the media was confirmed by education practitioners, who gave it a 93% rating of "very practical," and the student response questionnaires showed a 92% rating of "very practical." The N-Gain test from pretest and posttest scores showed an N-Gain of 0.75, indicating effectiveness.In conclusion, the LKPD based on the Learning Cycle 5E model is highly valid, practical, and effective for biology learning, with positive feedback from both teachers and students and significant improvements in learning outcomes.